2014
DOI: 10.1155/2014/686921
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Fruit as a Rich Source of Biologically Active Compounds

Abstract: Pomegranate is a widely used plant having medicinal properties. In this review, we have mainly focused on the already published data from our laboratory pertaining to the effect of methanol extract of pericarp of pomegranate (PME) and have compared it with other relevant literatures on Punica. Earlier, we had shown its antiproliferative effect using human breast (MCF-7, MDA MB-231), and endometrial (HEC-1A), cervical (SiHa, HeLa), and ovarian (SKOV3) cancer cell lines, and normal breast fibroblasts (MCF-10A) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(134 citation statements)
references
References 94 publications
4
113
1
1
Order By: Relevance
“…The edible part of pomegranate fruit accounts for 15–40% of its total weight, of which water accounts for approximately 79% and carbohydrates account for 7%, and it is also rich in fatty acids, vitamin and mineral elements, soluble solids, and organic acids. More than 60 functional components have been identified in pomegranate and can be divided into 7 categories: phenols, flavonoids, alkaloids, vitamins, triterpenes, sterols, and unsaturated fatty acids . Polyphenols are one of the most abundant active components of pomegranate.…”
Section: Active Components Of Pomegranatementioning
confidence: 99%
“…The edible part of pomegranate fruit accounts for 15–40% of its total weight, of which water accounts for approximately 79% and carbohydrates account for 7%, and it is also rich in fatty acids, vitamin and mineral elements, soluble solids, and organic acids. More than 60 functional components have been identified in pomegranate and can be divided into 7 categories: phenols, flavonoids, alkaloids, vitamins, triterpenes, sterols, and unsaturated fatty acids . Polyphenols are one of the most abundant active components of pomegranate.…”
Section: Active Components Of Pomegranatementioning
confidence: 99%
“…From an initial pool of 80 foods retrieved by the other FFQs, a number of typical foods and highly consumed by the Sicilian inhabitants were lacking. Among them, we included some fruits that typically grow in the Sicilian area and demonstrated important health benefits, such as red oranges (Grosso et al 2013), prickly pears (Feugang et al 2006), pomegranates (Sreekumar et al 2014), artichoke (Rondanelli et al 2013) and some characteristic foods that may have peculiar nutritional profile [i.e. ''ricotta'' whey cheese have less fats than more common cheeses (Madalozzo et al 2015)].…”
Section: Food Frequency Questionnairementioning
confidence: 99%
“…The fruit itself is a rich source of two types of polyphenolic compounds: anthocyanins (such as delphinidin, cyanidin, and pelargonidin), which give the fruit and juice its red color, and hydrolyzable tannins (such as punicalin, pedunculagin, punicalagin, gallagic, and ellagic acid), which account for 92% of the antioxidant activity of the whole fruit [24, 25]. Studies have also shown that the antioxidant capacity of pomegranate juice is three times that of the popular antioxidant-containing beverages such as red wine and green tea, presumably due to the presence of hydrolyzable tannins in the rind, along with anthocyanins and ellagic acid derivatives [25-27]. In a comparative analysis, anthocyanins from pomegranate were also shown to possess higher antioxidant activity than vitamin-E (a-tocopherol), ascorbic acid and 3-carotene [26].…”
Section: Introductionmentioning
confidence: 99%